Methods of nutritional evaluation between patients in hemodialysis - Bertoni, Vanessa Maria; Bettinelli, Luiz Antonio; Pasqualotti, Adriano; Kayser, Anelise (O Mundo da Saúde, 2017)
Chronic kidney disease is a public health problem. Characterizing the nutritional profile of these patients allows early diagnosis of possible nutritional risks. The objective was to evaluate the nutritional status and dietary intake of hemodialysis patients. A cross-sectional study was performed at a hemodialysis clinic from February to April 2016. Patients 18 years of age or older who underwent treatment for at least three months and were able to perform the Bioimpedance test were included. Nutritional status was determined by Body Mass Index. The Palmar Grip Strength was measured by dynamometer and the Adductor Muscle Thickness of the Thumb was by an adipometer, food intake was analyzed through a 24-hour Food Recall. A Global Subjective Assessment was performed, adapted for kidney patients. Of the 33 patients, 66.7% were males, with a mean age of 57.6 ± 14.2 years. According to the body mass index, eutrophy was prevalent (54.5%). The thickness of the adductor muscle of the thumb showed severe depletion (66.7%). Palmar grip strength ranked 72.7% of patients as malnourished. Body Fat, obtained through Bioimpedance, was high in 57.6%. The Global Subjective Assessment ranked 87.9% of patients with mild malnutrition. According to the 24-hour food recall, the total caloric intake averaged 1493 ± 530 Kcal. The protein mean was 0.88 ± 0.4 g / kg. The study allowed to visualize nutritional alterations, food intake below the recommended amounts, and different classifications of the nutritional state depending on the method used. Thus, a comprehensive nutritional assessment becomes important.